Discovering the colliding wind binary HD 93129A - Marcote, B. (2015)
HD 93129A is a binary system including an O2 If+ and probably an O3.5 V-star orbiting at a distance of about 140 AU (55 mas given the distance of 2.5 kpc), which potentially makes the system the most massive one in the Galaxy, ahead of eta-Carina. Its non-thermal radio emission was proposed to be originated by the collision between the winds of both stars. HST/FGS data have been reanalyzed to derive an accurate absolute position of the stars to compare them with the radio emission. The analysis of ATCA radio observations along several years reveals a power-lawspectrum with an increase on the radio flux density along time. We conducted an observation with the Australian Long Baseline Array (LBA) at 2.3 GHz in 2008 to resolve the radio source and its location within the stellar system. These radio data revealed a bow-shape extended emissionlocated between both stars, as expected in a wind collision region. The observed structure allows us to roughly estimate the mass-loss rate ratio for the two stars in the system, concluding that dM_b/dt = 0.7 dM_a/dt. The multiwavelength analysis points out that the detected radio emission is likely to be originated by one of the most massive collision wind binary in the Galaxy.